Current commercial dPCR platforms: technology and market review. (3rd April 2023) - Tan, Li Ling; Loganathan, Nitin; Agarwalla, Sushama; Yang, Chun; Yuan, Weiyong; Zeng, Jasmine; Wu, Ruige; Wang, Wei; Duraiswamy, Suhanya
Abstract: Digital polymerase chain reaction (dPCR) technology has provided a new technique for molecular diagnostics, with superior advantages, such as higher sensitivity, precision, and specificity over quantitative real-time PCRs (qPCR). Eight companies have offered commercial dPCR instruments: Fluidigm Corporation, Bio-Rad, RainDance Technologies, Life Technologies, Qiagen, JN MedSys Clarity, Optolane, and Stilla Technologies Naica. This paper discusses the working principle of each offered dPCR device and compares the associated: technical aspects, usability, costs, and current applications of each dPCR device. Lastly, up-and-coming dPCR technologies are also presented, as anticipation of how the dPCR device landscape may likely morph in the next few years.